Changes in The Percentage of Spermato Genic Cells in White Mice Associated With Cadmium Administration - AI-Bairuty, J.A; Kadhim, A.H (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The effect of different doses (75,100,150 ppm) and periods oftreatment (3,6,9 days) on the spermatognic cells in white mice was studied. It was found that there was a significant decrease (P